Produção de 1,3-propanodiol por Klebsiella pneumoniae e Escherichia coli: otimização de meio e clonagem de genes - Avila Neto, Paulo Marcelo [UNESP] (2015)
Biodiesel glycerol can be used for the production of 1,3-propanediol by bacteria. In this study on the production of 1,3-propanediol by Klebsiella pneumoniae GLC29 was possible to optimize media culture the production of 1,3-propanediol using statistical experimental design techniques and response surface methodology, where 11 variables were tested and only 5 were found significant (glycerol, yeast extract, ammonium sulfate, vitamin B12 and fumarate). Subsequently, production of 1,3-propanediol was verified in 0,75 liter reactors, both in batch and exponential fed-batch. It was possible to achieve 23.6 g/L of 1,3- propanediol in batch cultures using pure glycerol, 27 g/L of 1,3-propanediol in batch cultures using biodiesel glycerol, and 29.9 g/L of 1,3-propanediol in exponential fed-batch using biodiesel glycerol. Also, it was possible to amplify and clone all the genes responsible for the production of 1,3-propanediol by Klebsiella pneumoniae GLC29 in a plasmid, using Gibson assembly, a recent isothermal assembly methodology. The genes were expressed in Escherichia coli strains, and it was then verified the production of 1,3-propanediol in flasks and bioreactors, in which it was possible to reach 11 g/L 1,3-propanediol produced by E. coli SZ63 with the plasmid pSB1C3-dhaB1234TFG in fed-batch cultures